Parties, Candidates, and Constituency Campaigns in Canadian Elections. (UBC Press, 1998)
Political scientists have traditionally examined the democratic process at the macro level. With its unique micro-level focus, Parties, Candidates, and Constituency Campaigns in Canadian Elections provides the first systematic analysis of the local constituency campaigns that are the basis of elections and democracy in Canada. By taking a detailed look at campaigns in seven B.C. ridings during the 1988 "free-trade" election -- the last under the old three-party system -- Anthony Sayers develops a typology of candidates and campaigns. The dynamics of local associations, nominations, and campaigns, including those of former prime minister Kim Campbell and New Democrat Svend Robinson, as well as key strategic events and the role of the media, are reconstructed from interviews with candidates, campaign managers, party strategists, volunteers, and journalists. The 1993 and 1997 elections are then invoked to show that the insights drawn about the nature of constituency politics remain relevant to the new party system. This important contribution to the study of Canadian elections forcefully argues that knowledge of the dynamics at the local level is essential to a full understanding of Canadian polity, its underlying social basis, and the factors that determine successful election campaigns. As such, Parties, Candidates, and Constituency Campaigns in Canadian Elections will intrigue not only political scientists and students of Canadian politics but also election candidates and party strategists.